Prothrombin complex concentrate for vitamin K antagonist reversal in traumatic intracranial hemorrhage - Beynon, Christopher; Nofal, Mohammed; Rizos, Timolaos; Laible, Mona; Sakowitz, Oliver; Unterberg, Andreas (Journal of clinical neuroscience, 2020)
Objective - Administration of prothrombin complex concentrate (PCC) is recommended for vitamin K antagonist (VKA) reversal in patients with severe bleeding complications. However, there are only limited data available on its use for VKA reversal in patients with traumatic intracranial hemorrhage (ICH). - Methods - Data from all anticoagulated patients referred to our hospital for treatment of traumatic ICH and who received PCC for anticoagulation reversal were retrospectively analysed with specific focus on bleeding and thromboembolic complications during the further in-hospital course. - Results - A total of 142 patients were included in the present study. The median age was 78 years (Interquartile range [IQR]: 72-84) and the median Glasgow Coma Scale (GCS) score on admission was 12 (IQR: 7-14). Median International Normalized Ratio (INR) on admission was 2.5 [IQR: 2.0-3.3] and decreased to 1.2 [IQR: 1.1-1.3] following administration of a median dose of 2000 I.U. PCC [IQR: 1500-2625]. The in-hospital mortality rate was 13% and the median GCS of survivors at discharge was 14 [IQR: 12-15]. Thromboembolic events after PCC administration occurred in 4 patients (2.8%). The overall one-year mortality rate in this patient cohort was 49%. - Conclusions - PCC administration rapidly normalises INR and facilitates urgent neurosurgical procedures in anticoagulated patients with traumatic ICH.
Gesehen am 18.11.2020